Mooring positioning performance of jack-up platform. (2nd July 2020) - Tang, Wenxian; Zhuang, Hong; Tang, Zhenxin; Guo, Sheng; Yan, Fei
ABSTRACT: This study focussed on the mooring positioning of a jack-up platform. A numerical analysis was performed using ANSYS to examine the performance of a mooring system in time and frequency domains. The hydrodynamic response of the platform was analysed, and response amplitude operators were obtained in the frequency domain. A coupling analysis of platform motion was performed in the time domain, which examined the effects of environmental loading directions on platform displacements and the influence of mooring line parameters on mooring positioning performance. The primary concern was effects of the incident angle of environmental load on six components of platform displacement and mooring line tension. Moreover, a multi-objective optimisation technique was employed to control the length and tension of the mooring line in towing and positioning, which can determine the optimal length of the mooring line and then assist in achieving accurate platform positioning and steady mooring.